Apakah Profitabilitas dan Ukuran Perusahaan Berkontribusi terhadap Nilai Perusahaan? - Ishak, Jouzar Farouq; Dahtiah, Neneng; Sitorus, Sifra Christalia Rustiana; Nabila, Raihani Putri (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
The purpose of this research is to examine the effect of profitability and size company on the firm value of company in Index LQ-45 Indonesia Stock Exchange. This research uses financial statements data in term 2018-2023 by multiple regression analysis. The result shows that profitability and size company have effects on the firm value of company in LQ-45 Index Indonesia Stock Exchange. A company size that is too large is considered to cause a lack of efficiency in monitoring operational and strategic activities by management, thereby reducing firm value.